2009
DOI: 10.1055/s-0028-1104532
|View full text |Cite
|
Sign up to set email alerts
|

Laughter and Communicative Engagement in Interaction

Abstract: We examined if and how laughter functioned communicatively as an indicator of engagement in group interactions involving adults with traumatic brain injury (TBI). Engagement refers to the intensity and manner of interpersonal involvement displayed by participants in social situations, and it reflects the extent to which they are mutually engrossed in, and alive to, the unfolding interaction. Analysis revealed that laughter functioned communicatively to support the "face," or public self-image, of those with TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Human laughter is generally viewed to communicate a sender’s message non-verbally and can be considered a multifaceted and complex social behavior that shapes group structures during social interaction (Szameitat et al, 2009). Conceptualizing laughter as a distinct form of communication could help to illuminate nurses’ understanding of how a PWCI and caregiver engage with one another, giving insight into the interpersonal relationship of the dyad (Kovarsky, Curran, & Nichols, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Human laughter is generally viewed to communicate a sender’s message non-verbally and can be considered a multifaceted and complex social behavior that shapes group structures during social interaction (Szameitat et al, 2009). Conceptualizing laughter as a distinct form of communication could help to illuminate nurses’ understanding of how a PWCI and caregiver engage with one another, giving insight into the interpersonal relationship of the dyad (Kovarsky, Curran, & Nichols, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…, Kovarsky et al . , , , Rönfeldt , Simmons‐Mackie and Damico ). Investigations have focused on what Goffman () calls ‘considerateness’ or the actions participants take to safeguard their interlocutors public status as people who are well regarded, while ‘pride’ (Goffman ) or the actions participants take to safeguard their own respect‐worthy personas has not received any attention.…”
Section: Discussionmentioning
confidence: 99%
“…For example, during individualized aphasia therapy, Simmons-Mackie and Schultz (2003) found that humor served "to lubricate the therapy process" (p. 751) by building solidarity, mitigating embarrassment, and soliciting cooperation with tasks. In a prior study of group interactions involving adults with TBI, selfdeprecating humor and good-natured teasing helped to minimize social distance and promote the face of the participants (Kovarsky et al 2009). Other research showed that, among adults with aphasia taking part in group therapy, humor coupled with laughter signaled their positive engagement in the therapeutic process (Simmons-Mackie & Damico, 2009).…”
Section: Topics In Language Disorders/october-december 2011mentioning
confidence: 97%
“…Student staff were told it was permissible to promote lighted-hearted, joking relationships, similar to those found among adult friends (Straehle, 1993), to foster group camaraderie. As a result, interactions often were characterized by good-natured teasing and laughter (Kovarsky et al, 2009). It is important to note that these students were not in a traditional training setting where they Copyright © 2011 Lippincott Williams & Wilkins.…”
Section: Collecting and Examining The Datamentioning
confidence: 99%